Bacteriophage and nanotechnology in the management of COVID-19: A Review Article - Zghair, Abdulrazzaq; Kasim, comSumayah (University of Thi-Qar Journal of Science, 2022)
An international panic has been sparked by the Covid-19 virus outbreak regarding our knowledge and preparedness against virus outbreaks and be calls whole scientific community to level up fight against this giant killer. Scientists are exhaustively testing already available drugs efficient associated diseases, the coronaviruses that cause severe acute respiratory syndrome (SARS-CoV) and MERS-CoV (Middle East Respiratory Syndrome Coronavirus) (MERS-CoV) and a concrete solution here too is outlying. In the present scenario nanotechnology envisages a more practical approach towards treatment of severe cases of covid-19. Bacteriophages have the innate capacity to regulate immunity and their nanoscale size makes them perfect candidates to peruse as nanomedicine against the severe cases of COVID-19.